Bonus caps, deferrals and bankers' risk-taking - Esa Jokivuolle; Jussi Keppo; Xuchuan Yuan (Bank of Finland, 2015)
Regulators restrict bankers' risk-taking by bonus caps or deferrals. We derive a structural model to analyze these compensation regulations and show that for a risk-neutral banker subject to positive switching costs of reducing bank risk, a bonus deferral is impotent while a sufficiently tight bonus cap reduces risk-taking. The model suggests that a bonus cap that equals fixed salary (as in the EU) reduces risk on average by 13% under conservatively calibrated positive switching costs. Further, the bonus cap would have considerably reduced risk-taking incentives in most US banks that did poorly during the global financial crisis. We also show that the bonus deferral is effective if the banker is risk-averse and the switching costs are not too high.
URN:NBN:fi:bof-201503041096
Keywords: G01; G21; G28; J33; M52; 330